Draft Annual Plan 1986-87 Volume II Agriculture and Co-operation Jammu and Kashmir Government - Planning Commission (Planning Commission, 1986)
Food grain production which was of the order of 5.82 lakhs tons during 1964-65 reached a level of 13.07 lakhs tons in 1980-81 i.e the first year of the 6th plan. However, subsequently the foodgrains production could not pick-up due to adverse weather conditions prevailing in various parts of the state, low consumption of fertilizers consequent upon price like of fertilizers and in-adequate development of irrigation facilities. During 1983-84 the total food production was thus estimated as only 12.90 lakhs tonnes. Achievement during 1984-85 are anticipated to be 12.51 lakhs tonnes and during 1985-86 as 12.36 lakhs tonnes, the reasons for low achievements during 1985-86 are the draught condition which has mostly affected the maize crop in Jammu division, on the basis of the strategy being followed for agriculture development and the level of achievements made in the past the targeted proposed for 1986-87 is 14.24 lakhs tonnes.
Jammu and Kashmir Government, Planning and Development Department